Effects of Nigella sativa L. Seed Oil in Type II Diabetic Patients: a Randomized, Double-Blind, Placebo - Controlled Clinical Trial - MS Hosseini; SA Mirkarimi; M Amini; R Mohtashami; S Kianbakht; H Fallah Huseini (Institue of Medicinal Plants, ACECR, 2013)
Background: Nigella sativa (N. sativa) seeds are used to treat diabetes mellitus in traditional medicine. Moreover, N. sativa oil has reduced the fasting blood glucose level in non-diabetic volunteers. Objective: The present study was undertaken to explore the possible anti-hyperglycemic effect of N. sativa oil in type II diabetic patients. Methods: A randomized clinical trial was conducted in 70 type II diabetic patients referring to Baqiyatallah Hospital. The subjects were enrolled into two groups of 35 each. One group received 2.5 ml N. sativa oil and the other group received similarly 2.5 ml mineral oil two times a day for three months. The fasting and 2 hour postprandial blood glucose, glycosylated hemoglobin (HbA1c), lipid profile, BMI (body mass index), liver and renal function test were determined at the baseline and after three months. Results: The blood levels of fasting and 2 hours postprandial glucose and HbA1c were significantly decreased in the N. sativa group compared with the placebo group at the end of the study. The BMI of the N. sativa group was decreased significantly from baseline. No side effects were reported. Conclusion: N. sativa oil improves glycemic control in type II diabetic patients without any side effects.